2015
DOI: 10.1155/2015/342649
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Anticyclic Citrullinated Peptide Antibodies, Interleukin-6, Tumor Necrosis Factor-α, and C-Reactive Protein Are Associated with Increased Carotid Intima-Media Thickness: A Cross-Sectional Analysis of a Cohort of Rheumatoid Arthritis Patients without Cardiovascular Risk Factors

Abstract: The main cause of death in rheumatoid arthritis (RA) is cardiovascular events. We evaluated the relationship of anticyclic citrullinated peptide (anti-CCP) antibody levels with increased carotid intima-media thickness (cIMT) in RA patients. Methods. Forty-five anti-CCP positive and 37 anti-CCP negative RA patients, and 62 healthy controls (HC) were studied. All groups were assessed for atherogenic index of plasma (AIP) and cIMT. Anti-CCP, C-reactive protein (CRP), and levels of tumor necrosis factor alpha (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
(44 reference statements)
7
11
1
1
Order By: Relevance
“…In our population, we found a significant correlation between c-IMT and both ACPA and anti-CarP levels. Published data report an association with ACPA positivity and risk for CV events in RA [26]. Thus, the data reported in our study are in line with previous findings but, for the first time, extend the association of c-IMT to a new subset of autoantibodies (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our population, we found a significant correlation between c-IMT and both ACPA and anti-CarP levels. Published data report an association with ACPA positivity and risk for CV events in RA [26]. Thus, the data reported in our study are in line with previous findings but, for the first time, extend the association of c-IMT to a new subset of autoantibodies (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the study confirms an association between ACPA and cIMT in accordance with previous findings [26, 27]. …”
Section: Discussionsupporting
confidence: 92%
“…also reported that CIMT levels were higher in RA patients than in their control group. In yet another study Vázquez‐Del Mercado et al . demonstrated that CIMT levels were higher in RA patients than in their control group and that it showed a correlation with DAS‐28, a score used to assess the disease's activity.…”
Section: Discussionmentioning
confidence: 99%
“…Free oxygen radicals, released by the systemic inflammation process, have an important role in the progression of RA . A systemic inflammation process has direct effects on vascular, peripheral tissue and organs and this leads to endothelial damage, dysfunction and oxidative changes, all of which help the development of atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…This report is part of a larger project whose main objective is to assess predictors and evolution of CVD in RA patients. [ 9 , 10 ]…”
Section: Methodsmentioning
confidence: 99%